О граничном поведении открытых дискретных отображений с неограниченной характеристикой - Севостьянов, Е.А. (Український математичний журнал, 2012)
Вивчаються питання продовження вiдображень f:D→Rⁿ,n≥2, на межу областi D. За певних умов на вимiрну функцiю Q(x),Q:D→[0,∞], i межi областей D i D′=f(D), показано, що вiдкрите дискретне вiдображення f:D→Rⁿ,n≥2, яке має характеристику квазiконформностi Q(x), продовжується неперервним чином на межу ∂D. Отриманi твердження поширюють вiдповiдний результат У. Сребро для вiдображень з обмеженим спотворенням. We study the problem of extension of mappings f:D→Rⁿ¯, n ≥ 2, to the boundary of a domain D. Under certain conditions imposed on a measurable function Q(x), Q:D → [0, ∞], and the boundaries of the domains D and D′ = f (D), we show that an open discrete mapping f:D→Rⁿ¯, n ≥ 2, with quasiconformality characteristic Q(x) can be extended to the boundary ∂D by continuity. The obtained statements extend the corresponding Srebro’s result to mappings with bounded distortion.